Forecasting methods and applications - Makridakis, Spros G. (John Wiley & Sons, 1998)
"Since accurate forecasting requires more than just inserting historical data into a model, Forecasting: Methods and Applications, 3/e, adopts a managerial, business orientation. Integrated throughout this text is the innovative idea that explaining the past is not adequate for predicting the future."--BOOK JACKET. "Inside, you will find the latest techniques used by managers in business today, discover the importance of forecasting and learn how it's accomplished. And you'll develop the necessary skills to meet the increased demand for thoughtful and realistic forecasts."--BOOK JACKET. "New features in the third edition include an emphasis placed on the practical uses of forecasting; all data sets used in this book are available on the Internet; comprehensive coverage provided on both quantitative and qualitative forecasting techniques; and includes many new developments in forecasting methodology and practice."-